An investigation into the foundational principles of forensic science - Houck, Max Michael (Curtin University, 2010)
This thesis lays the groundwork for a philosophy of forensic science. Forensic science is a historical science, much like archaeology and geology, which operates by the analysis and understanding of the physical remnants of past criminal activity. Native and non-native principles guide forensic science’s operation, application, and interpretations. The production history of mass-produced goods is embedded in the finished product, called the supply chain. The supply chain solidifies much of the specificity and resolution of the evidentiary significance of that product. Forensic science has not had an over-arching view of this production history integrated into its methods or instruction. This thesis offers provenance as the dominant factor for much of the inherent significance of mass-produced goods that become evidence.